Factors influencing the activity patterns of two deer species and their response to predators in two protected areas in Indonesia - Rahman, Dede Aulia; Mardiastuti, Ani (THERYA, 2021)
Facing change of environmental conditions, the activity rhythm of animals may habituate. Remote cameras were used to quantify Bawean deer and red muntjac activity patterns and to examined differences by season, sex and lunar cycle to respond predator presence, in Bawean Island and Ujung Kulon National Park, Indonesia. Photographs of Bawean deer (n = 118) were taken during March to November 2014 and for red muntjac (n = 4,142) were taken during January 2013 to July 2014. Data were analyzed by using Generalized Additive Models (GAMs) to test the relationship between activity patterns and the lunar cycle, further, the pattern of daily activity overlap between deer and their predators calculated by kernel density estimation. The number of captures by camera trapping were less for both sexes of both deer in wet season. Male and female Bawean deer were active throughout the day and night during all seasons, with several activity peaks during the 24h period, while male and female red muntjac show diurnal activity levels with higher peaks 1h after sunrise until 1h before sunset. There was no significant difference in activities between males and females for both deer. The amount of nocturnal activity corresponding to differences in nocturnal luminosity for Bawean deer varied, but not for the red muntjac. Free-roaming dog and Bawean deer presented opposite peak activities, while dhole as (the predator of the red muntjac) and red muntjac were both cathemeral. The differences between the two similar-sized species could be closely related to reduction of predation risk and increasing foraging success.